A Trimly Fraud: “Breve historia de la literatura portátil”, 2 - Blesa, Túa (Tropelías: Review of Literary Theory and Comparative Literature, 2003)
This section continues the reading started in the first part of this paper by offering new cases of the exercise of quotation or plagiarism, that is, of re-writing, which is one of the most important characteristics of this novel. In addition to documenting those fragments which have been appropriated from other sources, the paper examines the condition, or conventions, of the historiographic text, which Vila-Matas’ novel parodies and makes manifest by inscribing itself within that genre but also by rejecting the realist style that characterizes the historiographic tradition. Thus, Matas’ novel opens this tradition up to other possible readings and interpretations.